Teori Psikologi Belajar dalam Menangani Permasalahan Akademik Melalui Layanan Bimbingan dan Konseling - Apriliana, Yona; N, Neviyarni; Nirwana, Herman (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Academic problems such as procrastination, learning burnout, and low student motivation have become major challenges in modern education. The urgency to understand and address these issues effectively highlights the importance of applying learning psychology theories within guidance and counseling services. This study aims to examine the utilization of learning psychology theories in addressing academic problems through a literature review of scholarly articles, academic books, and recent research reports. A qualitative approach was employed, using document analysis and thematic content analysis techniques. The findings indicate that behaviorist and cognitive theories have been partially applied, but are not yet fully integrated into practices in schools. This study offers a conceptual contribution by reinforcing theoretical approaches in academic counseling practices. The results imply the need for theory-based training for school counselors and suggest further in-depth field research to enhance practical application.